2020
DOI: 10.36227/techrxiv.13108238.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TOF-PET image reconstruction with multiple timing kernels applied on Cherenkov radiation in BGO

Abstract: Today Time-Of-Flight in PET scanners assumes a unique, well-defined timing resolution for all coincidence events. <br>However, recent BGO-Cherenkov detectors, combining prompt Cherenkov emission and the typical BGO scintillation signal, are capable of sorting events into multiple mixture timing kernels and therefore increase the available information for the image reconstruction. The number of Cherenkov photons detected per event impacts directly the signal rise time, which can therefore be used to impro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…As described earlier, the timing resolution depends on the energy deposition and sharing, leading to a complex TOF model for the scanner. However, here, the variety of timing resolutions obtained from the different combinations of detected events is much wider than in cases investigated previously [27], [43]. Efthimiou et al [27], [43], studying Cherenkov-based detectors [44]- [48], reported that the complexity of the reconstruction with multiple (25) kernels slowed down their convergence.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…As described earlier, the timing resolution depends on the energy deposition and sharing, leading to a complex TOF model for the scanner. However, here, the variety of timing resolutions obtained from the different combinations of detected events is much wider than in cases investigated previously [27], [43]. Efthimiou et al [27], [43], studying Cherenkov-based detectors [44]- [48], reported that the complexity of the reconstruction with multiple (25) kernels slowed down their convergence.…”
Section: Discussionmentioning
confidence: 67%
“…However, here, the variety of timing resolutions obtained from the different combinations of detected events is much wider than in cases investigated previously [27], [43]. Efthimiou et al [27], [43], studying Cherenkov-based detectors [44]- [48], reported that the complexity of the reconstruction with multiple (25) kernels slowed down their convergence. In this work, with only three Gaussian kernels, the Contrast Recovery Coefficient (CRC) converged slightly faster than the single and slower TOF kernel used for the BGO.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…For best image quality, a double Gaussian TOF kernel -as opposed to the conventional single Gaussian -had to be used because the time difference of the detected events in the Cherenkov detectors has long tails (Figure 10). A recent study has also successfully implemented a double Gaussian TOF kernel for BGO detectors while also exploring Gaussian mixture models [47]. In this study, the photo-detectors were modeled to be of negligible size, meaning that the detector with readouts at the sides (2-sided-top-bottom, 6-sided) had basically the same size compared to the detector with the readout at the back of the crystal.…”
Section: Discussionmentioning
confidence: 99%